Connected careers for the future [videorecording]. (New York Global Vision Production, 1997)
A guide to international careers for young people. Profiled in this video are remarkable people and their workplace. Presents the role model's high school and college education, internships, foreign language training and work and the mentors who helped them.
VHS.
Anchored by Charlayne Hunter Gault.
Keywords: Vocational guidance -- United States